Remodelling of membrane phospholipids during transition to diapause and cold-acclimation in the larvae of Chymomyza costata (Drosophilidae) - Kostál, Vladimír; Berková, Petra; Simek, Petr (Comparative biochemistry and physiology. Part B, Biochemistry & molecular biology, 2003)
The composition of molecular species of phosphatidylethanolamines (PEs) and phosphatidylcholines (PCs) was analysed in fat body and muscle tissues of Chymomyza costata larvae of different physiological states that markedly differed in their level of freeze-tolerance. Actively moving and feeding 3rd instar larvae had low (zero) capacity of freeze-tolerance and similar phospholipid (PL) compositions irrespective of their developmental destiny (non-diapause vs. diapause). Extensive remodelling of PL composition was found in these larvae in response to: (a) chilling of non-diapause larvae at 5 degrees C for 1 month; (b) developmental transition to diapause; and (c) chilling of diapause larvae. Transition to diapause and chilling led to an increase in freeze-tolerance. The increase in molar proportion of molecular species containing palmitic/linoleic (16:0/18:2) fatty acyls (FAs) esterified to sn-1/sn-2 positions of glycerol was the most prominent change, which was tightly statistically correlated with increasing freeze-tolerance. The increase of PLs with combination of 16:0/18:2 FAs was registered consistently in PEs and PCs in fat body and muscle tissues in response to chilling and to diapause onset. This increase was countered by a decreases of various molecular species, depending on tissue and lipid class. Most decreasing species shared one common theme: they had a saturated FA (palmityl, margaryl, stearyl) esterified at sn-1 position and a monounsaturate (palmitoleyl, oleyl) esterified at sn-2 position of glycerol. Possible adaptive meaning of PL molecular species remodelling is discussed.
Keywords: Cold Temperature; nízká teplota; aklimatizace; tuková tkáň; svaly; Animals; Larva; larva; Muscles; Phospholipids; Drosophilidae; Cell Membrane; fosfolipidy; Adipose Tissue; Acclimatization; zvířata; buněčná membrána